2010
DOI: 10.1007/s12035-010-8155-z
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis of Subarachnoid Hemorrhage Research: from Delayed Vasospasm to Early Brain Injury

Abstract: Delayed vasospasm that develops 3–7 days after aneurysmal subarachnoid hemorrhage (SAH) has traditionally been considered the most important determinant of delayed ischemic injury and poor outcome. Consequently, most therapies against delayed ischemic injury are directed towards reducing the incidence of vasospasm. The clinical trials based on this strategy, however, have so far claimed limited success; the incidence of vasospasm is reduced without reduction in delayed ischemic injury or improvement in the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
198
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(205 citation statements)
references
References 149 publications
2
198
0
5
Order By: Relevance
“…The results of our study were in line with those of previous reports as early brain injury treatment after SAH can attenuate some of the devastating secondary injuries from SAH such as vasospasm. 2,21,27 It has long been known that glutamate is detrimental to neurons following SAH. 9,16,34 In an in vitro study, baicalein has been demonstrated to have a protective effect against glutamate-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study were in line with those of previous reports as early brain injury treatment after SAH can attenuate some of the devastating secondary injuries from SAH such as vasospasm. 2,21,27 It has long been known that glutamate is detrimental to neurons following SAH. 9,16,34 In an in vitro study, baicalein has been demonstrated to have a protective effect against glutamate-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…27 Therefore, therapies focused on these early processes may prevent not only early brain injury but also reduce the development of the subsequent neurological sequelae.…”
mentioning
confidence: 99%
“…ROC curve analysis of the two studies revealed an AUC of 0.98 and 0.94, respectively [5,6]. The rupture of an intracranial aneurysm is associated with a sudden ICP increase and may reach values as high as 162 mmHg [3,21,22]. The sharp increase of ICP leads to a decrease of the cerebral perfusion pressure (CPP) with a consequent critical decrease of the cerebral blood flow (CBF) [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained as follows: Early brain injury after aSAH cannot be (over-) simplified to transient global cerebral hypoxia due to CBF decrease or arrest. There are several patho-physiological mechanisms that activate within minutes after the initial bleeding such as mechanical and bio-chemical trauma caused by the hematoma itself [3]. Furthermore, it is well known that patients with aSAH are specifically at risk of secondary neurological injury, which may be caused by 1) CVSdependent or -independent delayed ischemic events, aka DCI, 2) ''collateral damage'' in conjunction with the aneurysm securement, and/or 3) rebleeding [1,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation